Geography of Romanesque architecture (Bulletin KNOB, 1991)
The publication of the fourth volume of Romanische Baukunst am Rhein und Maas (Romanesque architecture on Rhine and Meuse) by Hans Erich Kubach and Albert Verbeek invites to a consideration which exceeds review limitations, for this volume is dedicated to Architekturgeschichte und Kunstlandschaft (History of Architecture and Geography of Art) and is the product of an implicit method, which varies on the classification of works of art based on geographical unities. This sort of classification is being practiced in German art-historical circles since the turn of the century. In the past such limitations were determined by the characteristics of races, the fixation of political, linguistic and ecclesiastical borders, the search for certain intentions in the social policy of emperors, kings, bishops and feudal lords.According to Kubach and Verbeek the buildings, their characteristics and spatial schemes, dictate the classification and have themselves grouped to geographical unities. With the publication of their catalogue (1976) of late-antique, pre-Romanesque and Romanesque architecture on the banks of Rhine and Meuse in the Federal Republic of Germany, Belgium, Luxembourg and the Netherlands they stated the unity of that architecture as an independent geography of art.In the fourth volume (1989) this unity is provided with argumentations by means of a very thorough comparative analysis of stylistic characteristics and similar forms.The stock of buildings is divided into four periods, a pre- and early Romanesque from about 1140 to 1200 and a late Romanesque from about 1200 to 1250. The pre- and early Romanesque architecture on Rhine and Meuse is part of a much larger European zone. The pre-Romanesque hall churches make up a continually growing coherent whole from the North Sea to the Loire and the Alps. The early Romanesque churches on Rhine and Meuse belong to Puig i Cadafalch's premier art roman (1928), which comprises Catalonia, Lombardy, Provence. Burgundy, Upper and Lower Rhine, but these churches profile themselves especially by the re-assimilation of late antique and Carolingian motifs from their own region.The high Romanesque architecture on Rhine and Meuse is an art with its own rudiments in the articulation of the wall, a building-up in storeys with mouldings and friezes. With its own preferences to the disposition of plan and spaces, which stand out sharply against the conceptions in Westphalen, the Scheldt area, Low Saxony and the banks of the Upper Rhine. In the first late Romanesque phase that character still was strengthened and in the second enheightened to a mannered liveliness and transparency, which runs parallel with the classical French gothic, but does not show a single congeniality with this style. This Romanesque geography of art is a network of equal buildings with one intentional attitude, one collective sensitiveness of forms, one Gesinnung. As a matter of course one thinks of Worringer's Kunstwollen or 'artistic volition'. Not for nothing the authors cite the novel Doktor Faustus of Thomas Mann, who makes his protagonists reflect on the destiny of German culture and the creation of einer untergründig wirkenden Gemeinsamkeit. This factor has been narrowed by the authors to an even smaller Gemeinsamkeit of the land of Rhine and Meuse from the 11th to the 13th century, whereby their experiences as students in the 1930's and as scholars in the 1940's unmistakably have determined their scientific habitus, which does not contain a reproach from the side of the reader because science and society cannot be separated. According to Kubach and Verbeek neither political, nor ecclesiastical territories play a role at that geographical framing of stylistic unity. Also the forms cannot be explained by certain wishes and ideals of patrons, a program of liturgical requirements or by the specific philosophy and religiosity of minsters and monastic orders.The iconological approach, which has been developed since Krautheimer's and Bandmann's publications and which establishes relations between buildings reaching far over local and regional borders (cp. Dutch studies as Aart Mekking's on the romanesque St. Servatius at Maastricht and the romanesque churches at Utrecht and Lex Bosman's on the Church of Our Lady at Maastricht) do not get Kubach and Verbeek's attention at their explanation of the origin of building forms.Since 1840 the geography of art was also practiced in France but went down at last after many polemics and modifications. In Germany the geography of art obtained special impulses from the political, social and cultural circumstances after the national defeats in World War l and II. Searching for a purified own identity, for rehabilitation, German historians of art separated the best artistic achievements from those of the neighbour states and thereby the Romanesque art from the medieval German empire was considered the most characteristic (by Georg Dehio in 1919 and Hans Jantzen in 1947), followed by a peculiar variant of gothic (Kurt Gerstenberg in 1913).He who supposes that this geography of art at the moment is not an issue anymore will be surprised by this new book by Kubach and Verbeek. Even if this sort of geography of art would appear to be untenable these monumental four volumes still are a wonderful accomplishment of two scholars, who spent a lifetime studying romanesque architecture. These perfectly published four volumes comprise an invaluable amount of thoroughly collected material and an abundance of drawings. They are an indispensible source for good. To the Netherlands, Belgium and Luxembourg this Standard work moreover has a special meaning the Romanesque architecture over there being considered a full-fledged part of the European Romanesque heritage.That the Dutch part of the inventory can be supplemented and corrected at the progress of research goes without saying. Who will take care of those supplements in set times? The two authors were in an old-fashioned way, with their own intellect, their own computus. The computer will have to keep their material up to date. The Deutscher Verlag für Kunstwissenschaft cannot be held responsible for that in its own course.